Religion and Individuals with Intellectual Disabilities An Exploratory Study of Self-Reported Perspectives - Shogren, Karrie A.; Rye, Mark S. (2005)
This study examined the religious beliefs and practices of forty-one people with mild and moderate intellectual disabilities. The results indicated that the majority of participants attended worship services, prayed, and rated religion as an important part of their lives. Ratings of the importance of religion were positively correlated with participation in religious activities. Participants tended to score high on measures of intrinsic religiosity, and used positive religious coping strategies more frequently than negative religious coping strategies. Individuals with mild intellectual disabilities identified significantly more abstract representations of religion than individuals with moderate intellectual disabilities. The implications of these findings for the inclusion of people with intellectual disabilities in religious activities are discussed along with future research directions.
Keywords: Religion; intellectual disabilities; Intrinsic religiosity; Religious Coping; Self-report